Motivational climate profiles, pubertal status, and well-being among female adolescent aesthetic sport athletes - Kipp, L. E.; Bolter, N. D.; Reichter, A. P. (Pediatric Exercise Science, 2019)
Purpose: Girls participating in aesthetic sports may be at risk for disordered eating and low self-esteem. Informed by self-determination theory, the authors examined motivational climate profiles to understand how climate dimensions differentially relate to psychological needs satisfaction, self-esteem, and disordered eating. Methods: Female gymnasts, divers, and figure skaters (N = 183; mean age = 13.5) completed a survey to assess perceptions of the motivational climate, perceived sport competence, autonomy, relatedness, self-esteem, and dieting. Pubertal status was assessed to control for developmental differences. Results: Three profiles emerged: High Important Role/Low Performance, High Effort and Cooperation/High Rivalry, and Low Mastery/High Unequal Recognition and Punishment. A 3 × 2 multivariate analysis of variance revealed profile groups significantly differed on perceived autonomy, coach relatedness, and teammate relatedness. In addition, perceived competence, self-esteem, and dieting significantly differed by pubertal status. For autonomy, the High Important Role/Low Performance group reported the highest scores. For coach and teammate relatedness, the Low Mastery/High Unequal Recognition and Punishment group reported significantly lower scores than the other 2 groups. Postpubertal girls reported lower sport ability and self-esteem and greater dieting. Conclusion: Physical maturity and social context were important in explaining girls` psychological needs satisfaction and well-being. Results add to the authors` understanding of the complex nature and influence of the motivational climate.